The ascorbate peroxidase–related protein: insights into its functioning in Chlamydomonas and Arabidopsis - Caccamo, Anna; Lazzarotto, Fernanda; Margis-Pinheiro, Marcia; Messens, Joris; Remacle, Claire (Frontiers in Plant Science, 2024)
We review the newly classified ascorbate peroxidase-related proteins (APX-R), which do not use ascorbate as electron donor to scavenge H2O2. We summarize recent discoveries on the function and the characterization of the APX-R protein of the green unicellular alga Chlamydomonas reinhardtii and the land plant Arabidopsis thaliana. Additionally, we conduct in silico analyses on the conserved MxxM motif, present in most of the APX-R protein in different organisms, which is proposed to bind copper. Based on these analyses, we discuss the similarities between the APX-R and the Class III peroxidases.